Incidence and Risk Factors of Low Birth Weight Among Babies Delivered at Tertiary Level Teaching Hospital in Nepal - Kayastha, Pawana; Manandhar, Sunil Raja (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Low birth weight is directly related to both immediate and long term development and wellbeing of a person. There are numerous maternal and foetal factors contributing to low birth weight. The mortality and morbidity of low birth weight can be reduced if the maternal risk factors are detected early and managed by simple techniques.Methods: 207 low birth weight live newborn babies regardless of gestational age born in a tertiary level teaching institute from September 2015 to September 2016 were enrolled as cases and same number of normal birth weight babies (i.e. 2.5 to 4 kgs) as control. Information was obtained directly from mothers using pretested structured questionnaire and was analysed using SPSS version 20.Results: The incidence of low birth weight was found to be 9.8%. Mean weight of low birth weight babies was 1.98 kg and mean gestational age was 37.34 weeks. Among low birth weight babies, 47.8% were preterm and 52.2% were term. Out of 119 small for gestational age babies, the frequency of symmetrical small for gestational age was 45.3% and asymmetrical small for gestational age was 54.6%. There was significant association of low birth weight with multiple maternal factors like maternal age, education, weight, height, weight gain during pregnancy, ANC visits, parity, antepartum haemorrhage, previous abortion/low birth weight, birth spacing, tobacco/alcohol intake and haemoglobin.Conclusions: Prevalence of low birth weight is likely to be far higher than figure in isolated rural settings of our country. Contribution of SGA is higher than Appropriate for Gestational Age which brings us to a larger burden of long term morbidity and mortality. Various maternal factors are responsible for birth of low birth weight babies.